Uniqueness and factorization method for inverse elastic scattering with a single incoming wave*Dedicated to the memory of Armin Lechleiter. (20th August 2019) - Elschner, Johannes; Hu, Guanghui
Abstract: The first part of this paper is concerned with the uniqueness to inverse time-harmonic elastic scattering from bounded rigid obstacles in two dimensions. It is proved that a connected polygonal obstacle can be uniquely identified by the far-field pattern corresponding to a single incident plane wave. Our approach is based on a new reflection principle for the first boundary value problem of the Navier equation. In the second part, we propose a revisited factorization method to recover a rigid elastic body with a single far-field pattern.